Analisis Kemampuan Berpikir Kreatif Siswa dalam Menyelesaikan Soal Open-Ended Ditinjau dari Gaya Kognitif - Oktaviana Putri, Anggita; Regina, Eka Putri (Mandalika Mathematics and Educations Journal, 2025)
The research is a qualitative research with a descriptive approach. The data analysis techniques used in this research are test data analysis techniques and interview data analysis techniques. This study aims to analyze students' creative thinking abilities in solving open-ended problems viewed from their cognitive styles, namely reflective and impulsive. The research was conducted at MTs Ash-Shiddiqi Rejoyoso with 16 students participating. Data collection techniques included MFFT (Matching Familiar Figures Test) to determine cognitive styles and a creative thinking ability test on the topic of two-dimensional figures. two students were selected as research subjects: one reflective students categorized as "very creative" and one impulsive students categorized as "fairly creative." The results showed that reflective students demonstrated better fluency, flexibility, and originality indicators than impulsive students. Reflective students were able to provide more varied solutions, accurate calculations, and produce unique shapes. In contrast, impulsive students tended to rush in solving problems, presented fewer solution variations, and displayed lower creativity in generating novel ideas. These findings suggest that cognitive style significantly influences students' creative thinking processes. This study is expected to serve as a reference for teachers to design learning strategies that can accommodate students' cognitive differences and encourage optimal creative potential development.